2023
DOI: 10.1158/1940-6207.capr-22-0435
|View full text |Cite
|
Sign up to set email alerts
|

PreCancer Atlas: Present and Future

Abstract: Precancer atlases have the potential to revolutionize how we think about the topographic and morphologic structures of precancerous lesions in relation to cellular, molecular, genetic, and pathophysiologic states. This mini review uses the Human Tumor Atlas Network (HTAN), established by the National Cancer Institute (NCI), to illustrate the construction of cellular and molecular three-dimensional atlases of human cancers as they evolve from precancerous lesions to advanced disease. We describe the collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In order to understand the cellular and molecular changes that occur from normal tissue to invasive disease across the spectrum of tumor development, the National Institutes of Health (NIH) Human Tumor Atlas Network is developing a precancer atlas with several centers across the country focusing on different premalignant tumor types. [49][50][51] Bulk RNA sequencing of 150 bronchial biopsies indicated that precancer dysplastic lesions can be grouped into four molecular subtypes: proliferative, inflammatory, secretory, and normal. Notably, similar subtype-specific gene expression patterns were seen in matched distant areas of the lung that were grossly pathologically normal, consistent with a field effect on the entire lung.…”
Section: Identification Of the Immune Microenvironment In Premalignancymentioning
confidence: 99%
“…In order to understand the cellular and molecular changes that occur from normal tissue to invasive disease across the spectrum of tumor development, the National Institutes of Health (NIH) Human Tumor Atlas Network is developing a precancer atlas with several centers across the country focusing on different premalignant tumor types. [49][50][51] Bulk RNA sequencing of 150 bronchial biopsies indicated that precancer dysplastic lesions can be grouped into four molecular subtypes: proliferative, inflammatory, secretory, and normal. Notably, similar subtype-specific gene expression patterns were seen in matched distant areas of the lung that were grossly pathologically normal, consistent with a field effect on the entire lung.…”
Section: Identification Of the Immune Microenvironment In Premalignancymentioning
confidence: 99%